Corporate groups, dual-class shares and the value of voting rights - Nicodano, Giovanna (Journal of Banking & Finance, 1998)
It is known that deviating from the one-share–one-vote principle through the issue of non-voting stock increases the value of outsiders' voting rights. We argue that the creation of a business group is another way to deviate from one-share–one-vote and we show that it produces a larger voting-share premium in holding companies. As a consequence, having both subsidiaries and non-voting stock produces a multiplier effect on the voting premium. The puzzling size of the premium in Italy was never related to the interaction of pyramiding and non-voting stock. Our empirical study confirms that the premium is larger for holding companies issuing non-voting stock than for similar operating companies without non-voting equity.